Application of the Monte-Carlo simulation for the statistical testing of the hypothesis that a steady-state distribution of the number of customers in the queueing system GI=G=1 tends to the normal distribution in the case of heavy traffic - Kuznetsov, I. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
The queueing system GI/G/∞ in a heavy traffic is considered. A statistical testing of the hypothesis that a steady-state distribution of the number of customers tends to the normal distribution is proposed. The χ2-criterion enables us to determine a minimal load, from which the statistical data don’t contradict this hypothesis.